(3eaGJjM GdCUhds - (3GdWHGWHGFj GdcQHdGFj, GdeLGgO, eMeO Hf Ydj Hf eMeO Hf Ydj, J (B1242 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B...(3HGH eaGJjM GddZGJ ; bGd Gddg JHGQc hJYGdi (B{ (3heG CQSdfG ef QShd EdG HdSGf bheg (B} (3Gdbhd aj GdOdGdI (B: (3GNJda GdYdeGA aj Cf GddaX gd jOd Ydi eYfGg HGdPGJ Ch HhVY GdhGVY Ydi bhdjf (B...s
(3BNQgG (B:s
... (3hbO GJab cGaI GdfGS Ydi Pdc hPcQ eKGdG BNQ abGd hceG (B... (3Ke SfI ef Sff GdYHGOI dG jchf fSNG dJdc GdYHGOI (B... (3Gdhbha Ydi jejf GdEeGe aj GdUdGI (B. (3GfJgis
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\543s
(3EjVGM Gdecfhf (B2\520s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs